Recurrence of atrial fibrillation following pulmonary vein isolation: impact of body mass index on one- and three-year outcomes. (3rd October 2022) - Milstein, N; Saberito, M; Bhatt, A; Habibi, M; Sichrovsky, T; Preminger, M; Shaw, R; Mittal, S; Musat, D
Abstract: Background: Cryoballoon (CB) pulmonary vein isolation (PVI) is an accepted method for ablation in patients with paroxysmal and persistent atrial fibrillation (PAF, PeAF). However, there are a paucity of data about the impact of body mass index (BMI) on one-year and longer-term outcomes following ablation. Objective: To objectively understand the impact of BMI on outcomes following CB PVI. Methods: We enrolled consecutive AF patients undergoing CB PVI; all patients had an implantable loop recorder (ILR), which transmitted data wirelessly daily. We assessed AF recurrences after excluding an initial 3-month post-ablation blanking period. Results: The cohort included 222 pts (66±9 years; 143 [64%] male; 120 [54%] PAF; CHA2DS2-VASc 2.6±1.6). The mean BMI was 30±5. Patients were followed for 763±347 days, during which time 50% and 68% had recurrent AF 1- and 3-years post ablation. We divided the cohort based on the mean BMI into 2 groups: BMI <30 and BMI >30. Heavier patients were younger and more likely to have PeAF. Over 1-year of follow-up, patients with a BMI <30 had similar likelihood of being free of AF to patients with a BMI >30 (46% vs, 56%, p=0.0.097, Figure 1, left). However, as patients were followed for 3-years, freedom from AF was significantly higher in patients with a BMI <30 (59% vs. 81% in BMI >30, p=0.002, Figure 1, right). Conclusions: Our data show that although patients had similar outcomes 1-year post-ablation, during longer-term follow-up patients with a BMI >30 had a much worse outcome. Our study uniquely offers objective (using an ILR) assessment of the impact of BMI on long-term outcomes following CB PVI (homogenous ablation strategy). These data highlight the need to identify strategies to improve outcomes in obese patients. Funding Acknowledgement: Type of funding sources: None.